Flooding as a Natural and Moral Evil: A Philosophical and Ethical Analysis of the Ogunpa Floods in Ibadan, Nigeria - Oyebanji, Israel Temitope (Scriptura Indonesia, 2023)
This study investigates the Ogunpa floods in Ibadan as a manifestation of both natural hazard and moral failure, situated within environmental ethics and philosophical discourse. Flooding, though natural in origin, is increasingly intensified by human actions such as deforestation, poor waste management, and urban planning violations, rendering it a subject of ethical scrutiny. While existing research focuses on hydrological and engineering perspectives, a critical gap remains in integrating philosophical frameworks, particularly free will, determinism, and moral responsibility into flood analysis. This research asks: To what extent are recurrent floods in Ibadan a result of human moral failure rather than mere natural occurrence? Employing qualitative analysis, the study draws on philosophical reasoning, environmental ethics, and case study methodology, engaging with Urban Resilience Theory to evaluate systemic vulnerabilities. The key finding is that the Ogunpa floods are not purely natural disasters but are significantly exacerbated by avoidable human decisions, thus constituting a form of moral evil. The paper concludes that sustainable flood mitigation requires not only infrastructural interventions but ethical accountability and proactive governance. Recommendations include institutionalising disaster risk management, enforcing planning laws, and public education on environmental stewardship.